Advokasi Sosial Dalam Pemenuhan Hak Atas Identitas Anak Di Yayasan Bina Anak Pertiwi - Widiah Nur Halimah; Moh. Amin Tohari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Social advocacy is carried out to provide change by defending victims of injustice. One of the social problems is the number of street children which increases every year. Children spend their time on the streets, without complete identification as their civil right, so it is difficult to be identified. Therefore, the Pertiwi Child Development Foundation provides social advocacy services to assisted children to achieve child welfare. This research aims to determine and analyze the implementation of social advocacy carried out by the Bina Anak Pertiwi Foundation in fulfilling the right to identity and analyze obstacles in social advocacy. Data collection techniques include observation, interviews and documentation with a qualitative approach. The results of this research show that the implementation of social advocacy in fulfilling children's rights to identity at the Bina Anak Pertiwi Foundation includes identifying problems, formulating solutions, building awareness and political will, implementing policies, and evaluating. The inhibiting factors for social advocacy are lack of funding and lack of human resources. The supporting factors are external and internal parties who are able to work together in the relief process.